The Impact of Comprehensive Agrarian Reform (CARP) on the Crop Sector - Maria Piedad S. Geron (Philippine Institute for Development Studies (PIDS), 1994)
Several studies have shown that land reform has a positive impact on rice and corn productivity. However, the same cannot be said in sugar and coconut areas. This paper attempts to verify the effect of the implementation of CARP on the productivity of sugar and coconut farms. To answer the productivity issue, the study examines whether agrarian reform beneficiaries have access to credit and new technologies and whether the transfer of ownership under CARP has affected the collateral value of land.
Keywords: 330; productivity; coconut industry; land management; collateral; credit market; sugar products; crop production